Efeitos do período do ano e da raça da doadora na produção in vitro de embriões bovinos de corte e taxa de prenhez por transferência - Fernandes, Brenda Matos (2023)
Embryo transfer is a reproductive biotechnique widely used in cattle herds in Brazil, and approximately 98% of embryos are produced in vitro (IVP). However, the success of IVP is still quite diverse, and several factors need to be coordinated to obtain a live calf from an IVT embryo. The oocyte quality at the start of the process is one of the key factors, as well as the quality of the embryos, the recipients, and the environment where the animals are handled. The aim of this study was to evaluate the influence of the donor breed (Nellore vs. Senepol) and the time of year (Dry vs. Rainy) at the time of follicular aspiration (OPU) on the number of viable oocytes and embryos produced, as well as the pregnancy rate per embryo transfer (P/ET) of the recipients. Data from 368 Senepol and Nellore donors collected during 2021 at a commercial IVP laboratory located in the state of Minas Gerais, Brazil, was analyzed. Data collected included number of total and viable oocytes, number of viable embryos produced, embryo production rate and P/TE of the recipients. Seasons were divided into dry and rainy. The pregnancy diagnosis of the recipients was carried out 30 days after estrus. The data refused the normality assumptions based on Shapiro-Wilk's test and was then subjected to the Kruskal-Wallis’s test. P/TE was analyzed by Chi-square using R software (version 4.3.2). Statistical differences were characterized by P ≤ 0.05. A negative effect of the dry season was observed on the number of total and viable oocytes in the Nellore breed (P<0.05), and the viable oocyte rates were 6.72% lower in the Senepol breed and 3.99% lower Nellore during the dry season. The embryo production rate was lower for Senepol donors in both periods of the year (P < 0,05). The Nellore breed had a lower embryo production rate in the rainy period (P < 0.05). These differences in embryo production rate resulted in the same viable embryo production between the breeds in the different seasons analyzed. The P/TE was 13.68% percentage points lower for embryos from Senepol donors during the dry season, while the P/TE of embryos from Nellore donors was not affected by the season. In conclusion, the dry season negatively influences total and viable oocyte production in Nellore donors, while total and viable oocyte production in Senepol donors remained constant throughout the year. The embryo production of Nellore donors is negatively influenced by the rainy season, although it remains higher than the embryo production of Senepol donors throughout the year, and the P/TE of the embryos of Senepol donors is reduced during the dry season.